Republic of Kazakhstan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper analyzes the optimal policy response on the part of the Kazakhstan authorities to the prospective oil inflows. It surveys the literature on the so-called natural resource curse and offers an analysis of Kazakhstan's petroleum potential. The paper analyzes the impact of the oil boom on the non-oil sector, based on a general equilibrium model. It provides an analysis of fiscal rules and fiscal sustainability and assesses the possible role of fiscal policies in addressing the 'natural resource curse.'.